Joule heating-driven ultrafast synthesis of (Fe1−xMnx)2AlB2 and its electromagnetic wave absorption properties - Yuhang Bai; Zelong Yao; Yang Yang; Jinrui Li; Jia Liu; Peipei Wang; Huiling Du; Xing Zhao; Laifei Cheng (Journal of Advanced Ceramics)
Defect engineering enables the efficient management of electromagnetic parameters and the enhancement of electromagnetic wave (EMW) absorption. In this study, (Fe1−xMnx)2AlB2 transition metal boride (MAB) phases with a layered structure were prepared via Joule heating-driven ultrafast synthesis, and their EMW absorption properties were investigated. The experimental results demonstrate that the incorporation of Mn atoms at the M site can effectively modulate the impedance matching and EMW absorption properties of the material through the introduction of defects and lattice distortions. Notably, (Fe0.3Mn0.7)2AlB2 exhibits a reflection loss as high as −47.8 dB at 12.24 GHz, with a maximum effective absorption bandwidth of 4.16 GHz (10.24–14.40 GHz) at an ultrasmall thickness of 1.5 mm. This study provides a promising avenue for the development of excellent microwave-absorbing materials, which are essential for meeting the evolving requirements of advanced electronics. Additionally, this work offers a paradigm for enhancing other properties of MAB phases through defect engineering.